Engineering oxidoreductases: maquette proteins designed from scratch. (22nd May 2012) - Lichtenstein, Bruce R.; Farid, Tammer A.; Kodali, Goutham; Solomon, Lee A.; Anderson, J.L. Ross; Sheehan, Molly M.; Ennist, Nathan M.; Fry, Bryan A.; Chobot, Sarah E.; Bialas, Chris; Mancini, Joshua A.; Armstrong, Craig T.; et al.
Abstract : The study of natural enzymes is complicated by the fact that only the most recent evolutionary progression can be observed. In particular, natural oxidoreductases stand out as profoundly complex proteins in which the molecular roots of function, structure and biological integration are collectively intertwined and individually obscured. In the present paper, we describe our experimental approach that removes many of these often bewildering complexities to identify in simple terms the necessary and sufficient requirements for oxidoreductase function. Ours is a synthetic biology approach that focuses on from-scratch construction of protein maquettes designed principally to promote or suppress biologically relevant oxidations and reductions. The approach avoids mimicry and divorces the commonly made and almost certainly false ascription of atomistically detailed functionally unique roles to a particular protein primary sequence, to gain a new freedom to explore protein-based enzyme function. Maquette design and construction methods make use of iterative steps, retraceable when necessary, to successfully develop a protein family of sturdy and versatile single-chain three- and four-α-helical structural platforms readily expressible in bacteria. Internally, they prove malleable enough to incorporate in prescribed positions most natural redox cofactors and many more simplified synthetic analogues. External polarity, charge-patterning and chemical linkers direct maquettes to functional assembly in membranes, on nanostructured titania, and to organize on selected planar surfaces and materials. These protein maquettes engage in light harvesting and energy transfer, in photochemical charge separation and electron transfer, in stable dioxygen binding and in simple oxidative chemistry that is the basis of multi-electron oxidative and reductive catalysis.